The response of winter wheat on the time of stunting autumn vegetation in the Northern Steppe of Ukraine - Mostipan, M. I. (Scientific Progress & Innovations, 2019)
The purpose of the article is to substantiate the scientific and methodological foundations of developing and introducing ecological-adaptive technologies of winter wheat cultivation and their correcting in the spring-summer period of vegetation, depending on the time of stunting the autumn vegetation and the duration of the winter dormancy state. Methods of the research. Winter wheat was grown after black fallow and corn for silage. Sowing was carried out in three terms: September 2 and 17 and October 2. The research results. It was proved that the terms of stunting autumn vegetation of winter wheat affect the yield capacity of winter wheat. When growing winter wheat after black fallow land and corn for silage, the highest yield capacity is formed during the years of stunting the autumn vegetation in the third decade of November, and the yield is respectively 5.67 and 5.58 t/ha. Earlier and later vegetation stunting causes the decrease of winter wheat yield. The lowest yield after two predecessors is formed in the period when the autumn vegetation stunts in the first decade of November. Different terms of sowing winter wheat differently influence the terms of autumn vegetation stunting. Of all the periods of the autumn vegetation stunting, the highest yield after black fallow was from the crops that were sown on September 17. Only during the years of very early autumn vegetation stunting of winter wheat, the crop sown on September 2 was more productive than when sown on October 2. Their yield capacities were respectively 5.17 and 4.68 t/ha. During all the years, with later stunting of autumn vegetation, the crop gave higher yields than at early sowing on September 2. When winter wheat was sown after the non-fallow predecessor of maize for silage during the years with early and late autumn vegetation stunting, the crop sown on September 2 gave higher yields than the crop that was sown on September 17 and October 2. When growing winter wheat on black fallow land in the Northern Steppe of Ukraine, the longer the condition of winter dormancy is, the lower is its yield capacity. During the years with dormancy period of up to 100 days the productivity was 5.92 t/ha, and during the years with the duration of this period more than 130 days it decreased to 4.16 t/ha. After corn for silage, the highest yields of winter wheat were obtained during the years with the period of winter dormancy from 111 to 120 days. Both the shortening and lengthening of the dormancy period caused the decrease of winter wheat yield after the non-fallow predecessor. The most significant decrease was observed during the years with the longest winter dormancy period duration and the yield was 4.48 t/ha. During the years with the duration of the winter dormancy to 100 days, the yield capacity of winter wheat on black fallow land increased as a result of shifting the sowing dates from earlier to later ones from 5.03 to 6.91 t/ha, and after corn for silage, on the contrary, it decreased from 4.05 to 3.46 t/ha. During the years with the duration of the winter dormancy for more than 100 days, the highest yield capacity after both investigated predecessors was received at sowing winter wheat on September 17. The productivity of winter wheat in the Northern Steppe of Ukraine depends on the duration of the period from the date of lowering the air temperature below 0 °C in autumn and its steady raising higher than 0 °C in spring. After two studied predecessors, the highest yield capacity of winter wheat was formed during the years with the duration of this period from 71 to 90 days and on black fallow land it was 5.89 t/ha, and after corn for silage – 4.95 t/ha. The reducing of this period to 70 and fewer days, as well as its extending for more than 90 days decreased the yield capacity of winter wheat after both predecessors. The longer was the period from stunting autumn vegetation to steady decreasing the air temperature below 0 °C, the higher was yield capacity of winter wheat. This pattern is characteristic of all the studied years of sowing after both predecessors. During the years with the duration of this period up to 10 days, the yield capacity on black fallow land was 4.09 t/ha, and after corn for silage it was 3.66 t/ha, while during the years with its duration for more than 20 days, it increased to 5.68 and 4.44 t/ha, correspondingly. The elements of scientific novelty. For the first time, for the conditions of the Northern Steppe of Ukraine, the classification of the terms for stunting the autumn vegetation of winter wheat was suggested and that their effect of sowing winter wheat at different time on its yield capacity was established. Practical value. The obtained research results create the scientific basis for correcting the technology of winter wheat cultivation in the spring-summer period, depending on the time of stunting the autumn vegetation and the duration of the winter dormancy period of plants.